HUBUNGAN EFIKASI DIRI DENGAN STRATEGI KOPING PADA PASIEN DIABETES MELLITUS TYPE 2 YANG MENGGUNAKAN INSULIN DI POLIKLINIK - Anisa; Nonok Karlina; Ahmad Syaripudin (Jurnal Kesehatan Mahardika, 2021)
Diabetes mellitus is a disease that has clinical signs and symptoms due to chronic declining function. Type 2 diabetes mellitus always increases every year as much as 9.3% of people. Patients with type 2 diabetes mellitus are required to always be routine control, but patients with diabetes mellitus will experience stress caused by various stressors, to reduce these problems interventions need to provide self-efficacy to patients and coping strategies are also needed so that patients are able to adapt to their stress in order to create coping strategies the good one.The purpose of this study was to determine the relationship of self-efficacy with coping strategies in patients with type 2 diabetes mellitus who use insulin in the Polyclinic of Waled District Hospital Cirebon. This type of research uses descriptive correlational with cross sectional approach. Sampling using purposive sampling technique amounted to 34 respondents. The instrument used was a questionnaire. Analysis of data using rank test speraman.Place of research in Waled District Hospital Cirebon in July 2020. The results showed that most respondents' self-efficacy in the high category (58.8%) and coping strategies were mostly in the good category (61.8%). Spearman rank test results P value <a and r <1 then H0 = rejected means that there is a strong and positive relationship between self-efficacy and coping strategies in patients with type 2 diabetes mellitus in the Polyclinic of Waled District Hospital Cirebon (P value = 0,000: a = 0 .05 r = 0.719). It is expected that nurses should provide more motivation and support to patients with type 2 diabetes mellitus and educate about the importance of coping strategies